A review on techno managerial approaches to energy optimization in chemical process industries - Parekh, Nishita; Kurian, Jinu; Patil, Rajesh; Gautam, Richa (Frontiers in Energy Research, 2023)
The chemical process industry, being energy intensive in nature, still struggles to consider energy management issues strategically and sustainably. Energy sustainability depends on sustainable energy supply, sustainable energy consumption and sustainable waste disposal. This paper focuses on analysing the current energy management and optimization scenario in industries and also attempts to identify the significance for incorporating energy management into the strategic perspectives of these industries through exhaustive literature review. To ensure optimization of energy, the paper illustrates the importance of adopting a techno-managerial approach, that integrates the technical aspects of energy conservation along with relevant management tactics. Further the paper is a preliminary study towards proposition of the framework for Indian chemical process SMEs, to systematically, overcome various challenges, and seize the available opportunities, to ensure the optimized energy utilization, thereby highlighting its long term and short term benefits. The suggestions in the paper would help these industries as well as the local and national level policy makers to improvise their energy footprint and make the world more energy sustainable.